Can MRI differentiate between ring‐enhancing gliomas and intra‐axial abscesses?. Issue 5 (4th May 2022) - Carloni, Andrea; Bernardini, Marco; Mattei, Chiara; De Magistris, Angela Vittoria; Llabres‐Diaz, Francisco; Williams, Jonathan; Gutierrez‐Quintana, Rodrigo; Oevermann, Anna; Schweizer‐Gorgas, Daniela; Finck, Cyrielle; Masseau, Isabelle; Lorenzo, Valentina; et al.
Abstract: Gliomas of the brain may appear as expansile ring‐enhancing masses in MRI studies, mimicking the appearance of intra‐axial abscesses. The aims of this study were to compare the MRI features of ring‐enhancing gliomas and intra‐axial brain abscesses in dogs and cats and to identify the characteristics that might help differentiate them. For this multicenter, retrospective, and observational study, the inclusion criteria were as follows: (a) a definitive diagnosis of glioma or abscess based on cytological or histopathological examination following CSF collection or surgical biopsy/necropsy, respectively; (b) MRI study performed with a high‐ or low‐field MRI scanner, including a same plane T1W pre‐ and postcontrast, a T2W and a T2 FLAIR sequence in at least one plane. If available, delayed T1W postcontrast, T2*W GE, DWI/ADC, and SWI sequences were also evaluated. Sixteen patients were diagnosed with ring‐enhancing gliomas, and 15 were diagnosed with intra‐axial abscesses. A homogenous signal on T1W ( P = 0.049) and T2W ( P = 0.042) sequences, a T2W ( P = 0.005) or T2*W GE ( P = 0.046) peripheral hypointense halo, and an even enhancing capsule ( P = 0.002) were significantly associated with brain abscesses. A progressive central enhancement on delayed T1W postcontrast sequences was correlated with ring‐enhancing gliomas ( P = 0.009). The combination of the following features was suggestive of brain abscess: homogeneous T1W or T2W signal intensity, a T2W or T2*W GE peripheral hypointense halo and an evenly enhancing capsule. Central progression of enhancement on delayed T1W postcontrast sequences was suggestive of glioma.